Linguagens em (con)fluência: o diálogo interartes em Catálogo de perdas e Aos 7 e aos 40, de João Anzanello Carrascoza - Caetano, Priscila Miranda (2023)
The work of João Anzanello Carrascoza is situated within an important framework of award-winning recent productions in Brazilian Literature. In his trajectory as a short story writer and novelist, the author presents us with marks that dialogue directly with our contemporaneity: the imagery language in his poetic prose; the hybridization of literary genres; reflections on writing and the act of writing; dialogue between languages in co-authorship processes. His collection of works directs us towards an active reading experience, wherein the reader is also invited to actively engage with and manipulate the book project as an artistic object. However, these trends are not new in the literary scene, given this, the first chapter of this work aims to present some productions that promote interart dialogue, at the intersection of literature with illustration, design, photography, cinema and the like, with the aim of analyzing and consolidating the interferences that one language exerts on the other, not only in the production of meaning, but in its entire structure, opening the fields of reader perception. In the second chapter, we analyze the work Catálogo de Perdas, in order to show the relationship between the short story, photography and graphic design in all its entirety. Finally, in the third chapter, the reader will come into contact with a cinematographic reading of the novel At 7 and 40, through the fusion of languages in the support of a graphic project that puts the reader in front of the windows, shots and scenes in movement, but also crystallized in time. In this path, we aim to prove the thesis that the interarts dialogue is not limited to the content of the works, but is established in the movement of assimilation of the syntax of one language in the other, within an anthropophagic process of writing